On the potential of a short‐term intensive intervention to interrupt HCV transmission in HIV‐positive men who have sex with men: A mathematical modelling study. Issue 1 (23rd August 2017) - Salazar‐Vizcaya, L.; Kouyos, R. D.; Fehr, J.; Braun, D.; Estill, J.; Bernasconi, E.; Delaloye, J.; Stöckle, M.; Schmid, P.; Rougemont, M.; Wandeler, G.; Günthard, H. F.; et al.
Summary: Increasing access to direct‐acting antiviral (DAA) treatment for hepatitis C virus (HCV) infection and decelerating the rise in high‐risk behaviour over the next decade could curb the HCV epidemic among HIV‐positive men who have sex with men (MSM). We investigated if similar outcomes would be achieved by short‐term intensive interventions like the Swiss‐HCVree‐trial . We used a HCV transmission model emulating two 12‐months intensive interventions combining risk counselling with (i) universal DAA treatment ( pangenotypic intervention ) and (ii) DAA treatment for HCV genotypes 1 and 4 (replicating the Swiss‐HCVree‐trial ). To capture potential changes outside intensive interventions, we varied time from HCV infection to treatment in clinical routine and overall high‐risk behaviour among HIV‐positive MSM. Simulated prevalence dropped from 5.5% in 2016 to ≤2.0% over the intervention period (June/2016‐May/2017) with the pangenotypic intervention, and to ≤3.6% with the Swiss‐HCVree‐trial . Assuming time to treatment in clinical routine reflected reimbursement restrictions (METAVIR ≥F2, 16.9 years) and stable high‐risk behaviour in the overall MSM population, prevalence in 2025 reached 13.1% without intensive intervention, 11.1% with the pangenotypic intervention and 11.8% with the Swiss‐HCVree‐trial . If time to treatment in clinical routine was 2 years, prevalence in 2025 declined to 4.8% without intensive intervention, to 2.8% with the pangenotypic intervention, and to 3.5% with the Swiss‐HCVree‐trial . In this scenario, the pangenotypic intervention and the Swiss‐HCVree‐trial reduced cumulative (2016‐2025) treatment episodes by 36% and 24%, respectively. Therefore, intensive interventions could reduce future HCV treatment costs and boost the benefits of long‐term efforts to prevent high‐risk behaviour and to reduce treatment delay. But if after intensive interventions treatment is deferred until F2, short‐term benefits of intensive interventions would dissipate in the long term.